Eighteen years’ experience with tumor treating fields in the treatment of newly diagnosed glioblastoma - Vymazal, Josef; Kazda, Tomas; Novak, Tomas; Slanina, Petr; Sroubek, Jan; Klener, Jan; Hrbac, Tomas; Syrucek, Martin; Rulseh, Aaron M. (Frontiers in Oncology, 2023)
The prognosis of glioblastoma remains unfavorable. TTFields utilize low intensity electric fields (frequency 150–300 kHz) that have an antimitotic effect, selectively inhibiting the growth of rapidly dividing tumor cells by disrupting multiple phases of the cell cycle and resulting in cellular apoptosis. TTFields are delivered via transducer arrays placed on the patients’ scalp. Between the years 2004 and 2022, 55 patients (20 female), aged 21.9–77.8 years (mean age 47.3±11.8 years; median 47.6 years) were treated with TTFields for newly-diagnosed GBM, and compared to 54 control patients (20 females), aged 27.0–76.7 years (mean age 51.4±12.2 years; median 51.7 years) (p=0.08). All patients underwent gross total or partial resection of GBM. One patient had biopsy only. When available, MGMT promoter, methylation status and IDH mutation was detected. Patients on TTFields therapy demonstrated improvements in PFS and OS relative to controls (hazard ratio: 0.64, p=0.031; and 0.61, p=0.028 respectively). TTFields average time on therapy was 74.8% (median 82%): median PFS of these patients was 19.75 months. Seven patients with TTFields usage ≤60% (23–60%, mean 46.3%, median 53%) had a median PFS of 7.95 months (p=0.0356). Control patients with no TTFields exposure had a median PFS of 12.45 months. Median OS of TTF patients was 31.67 months compared to 24.80 months for controls. This is the most extensive study on newly-diagnosed GBM patients treated with TTFields, covering a period of 18 years at a single center.